Proses Penyelesaian Sengketa Terhadap Pembagian Hak Waris Atas Tanah Yang Telah Dijual Oleh Salah Satu Ahli Waris (Studi Kasus Pengadilan Negeri Pemalang) - Priyono, Galih; , Nuswardhani, S.H, S.U (2017)
Inheritance arise due to the occurrence of events that happen to a person's death from family members, especially the elderly people that father and mother. If the deceased person's own property, the problem is not an event of death, but the assets left by the deceased. The provisions regarding the division of inheritance, that the division of inheritance is left entirely to the discretion of the testator himself in the moments before death as the provisions in the Civil Code thirteenth chapter of wills. In fact, in the community of what happened, although the implementation of inheritance have been there a will of the testator's estate or related division has created a collective agreement is still commonly arise disputes between heirs associated with the division of the inheritance. This study uses descriptive normative. Using secondary data and primary data. Data collection 2 techniques using literature studies, field studies and interviews. And using qualitative data analysis methods. Based on the results of research and discussion can be concluded that: First, the Court has obtained legal facts and concluded that the proven events occur disputed land purchase made by the Defendants. So that the judges stated that Defendant's actions constitute an unlawful act. Second, Control over the disputed land by the second defendant committed an act against the law. Third as a legal consequence that The Defendants or anyone who control the land in order to deliver to the plaintiff in an empty state.